Second free radial forearm flap for urethral reconstruction after partial flap necrosis of tube‐in‐tube phalloplasty with radial forearm flap: A report of two cases. Issue 1 (3rd September 2013) - Tchang, Laurent A.H.; Largo, René D.; Babst, Doris; Wettstein, Reto; Haug, Martin D.; Kalbermatten, Daniel F.; Schaefer, Dirk J.
Abstract : We present a salvage procedure to reconstruct the neo‐urethra after partial flap necrosis occurring in free radial forearm flap (RFF) phalloplasty for sex reassignment surgery. Two cases of tube‐in‐tube phalloplasty using a free sensate RFF are described in which partial flap necrosis occurred involving the complete length of the neo‐urethra and a strip of the outer lining of the neo‐phallus. Neo‐urethra‐reconstruction was performed with a second RFF from the contralateral side providing well‐vascularized tissue. No flap‐related complications were observed. Twelve months postoperatively, both patients were able to void while standing. A satisfactory aesthetic appearance of the neo‐phallus could be preserved with an excellent tactile and erogenous sensitivity. Using this technique, we successfully salvaged the neo‐urethra and reconstructed the outer lining of the neo‐phallus © 2013 Wiley Periodicals, Inc. Microsurgery 34:58–63, 2013.